Strategic intelligence management : national security imperatives and information and communications technologies - Akhgar, Babak; Yates, Simeon (Butterworth-Heinemann, 2013)
This book introduces both academic researchers and law enforcement professionals to contemporary issues of national security and information management and analysis. It provides the background, analysis, and insight on specific topics and case studies, exploring the technological and social aspects of managing information for contemporary national security imperatives.